STRATEGI PEMBELAJARAN EKSPOSITORI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V PADA PELAJARAN PAI DI SDN GUNUNG KONENG KOTA TASIKMALAYA - Jani Sanjari (HASBUNA : Jurnal Pendidikan Islam, 2025)
Education is essential for the nation to increase competitiveness in various fields. Developed countries continue to invest in education. Islamic religious education has a major role in shaping students who are noble and law-abiding. A teacher must use the teaching materials of the Qur’an and Hadith to educate students about virtue. Learning motivation is very important, so that students do not consider learning boring. Expository learning strategies involve verbal delivery of materials by teachers to help students understand lessons. At SDN Gunungkoneng City Tasikmalaya, the motivation for students is still low, so research aims to increase the motivation of learning through this strategy. The right strategy can create interesting learning. The study focuses on implementing expository learning strategies for the motivation of grade V students in Islamic Religious Education. This research motode uses descriptive analysis methods, because its nature uses descriptive analysis methods in other words, this research seeks to describe, outline an ongoing state of affairs that are based on facts and information obtained from the field and then analyze based on variables from one another. The results of the study in the field are PAI Teacher at SDN Gunungkoneng City Tasikmalaya using expository learning strategies, which include lectures, discussions and question answers. The motivation of learning class V students is good, even though there are less. Teachers strive to improve students’ motivation and learning outcomes by choosing the right method.